Jawabanmu

2014-09-04T17:53:56+07:00
Prinsip jajargenjang: 2sisi yang berhadapan sama panjang
*sisi yang sama:
KL=MN=TU=RS
KN=LM=RU=ST

A. 
-KN=4cm karena KN=LM=4cm
-MN=6cm karena MN=KL

B.  \frac{KL}{RS}  \frac{LM}{ST}
 \frac{6cm}{15cm}  =  \frac{4cm}{ST}
6cm x ST = 15cm x 4cm
ST =  \frac{60cm}{6cm}
ST = 10cm





Prinsip jajargenjang: 2sisi yang berhadapan sama panjang
*sisi yang sama:
KL=MN=TU=RS
KN=LM=RU=ST

A. -KN=4cm karena KN=LM=4cm
-MN=6cm karena MN=KL

B. [tex] \frac{KL}{RS} [/tex] = [tex] \frac{LM}{ST} [/tex]
[tex] \frac{6cm}{15cm} [/tex] = [tex] \frac{4cm}{ST} [/tex]
6cm x ST = 15cm x 4cm
ST = [tex] \frac{60cm}{6cm} [/tex]
ST = 10cm
Prinsip jajargenjang: 2sisi yang berhadapan sama panjang
*sisi yang sama:
KL=MN=TU=RS
KN=LM=RU=ST

A. -KN=4cm karena KN=LM=4cm
-MN=6cm karena MN=KL

B.[tex] \frac{KL}{RS} [/tex] = [tex] \frac{LM}{ST} [/tex]
[tex] \frac{6cm}{15cm} [/tex] = [tex] \frac{4cm}{ST} [/tex]
6cm x ST = 15cm x 4cm
ST = [tex] \frac{60cm}{6cm} [/tex]
ST = 10cm
TU=15cm karena TU=RS
RU=10cm karena RU= ST